Dampak Politik Identitas pada Pilkada (Studi Kasus Politik Identitas Pasangan Akhyar-Salman pada Pilkada 2020 di Kota Medan) - Aminah Aminah; Feby Gustira Harahap; Effendi Hasan; Muliawati Muliawati; Ubaidullah Ubaidullah (Jurnal Community, 2022)
In the 2020 Pilkada in Medan City, the Akhyar-Salman candidate pair collaborated with UAS in campaigning activities to attract the sympathy of recitation mothers and Muslims in Medan City. The uniqueness of this research is that the practice of identity politics carried out by Akhyar-Salman has no effect on the victory in the 2020 Pilkada in Medan City. The purpose of this study is to validly reveal the practice and influence of the identity politics of the Akhyar-Salman couple in the 2020 Pilkada in Medan City. The research method carried out by the researcher is a qualitative method through observation, interviews and documentation. The results of this study indicate that the identity politics practices carried out by the Akhyar-Salman couple in the 2020 Medan City Elections include (1) door to door, (2) social media, (3) issue management. Then the influence of identity politics did not make the Akhyar-Salman pair get a seat in the Medan City Election. The indication of this problem is that there is power driven by power, so the Boby-Aulia pair have slightly different votes. Even though during the campaign period they used a fairly strong strategy of identity politics, but this was not able to have an effect on the votes they got and irrational promises.